Investigation of the behavior of effective charge of Aditya tokamak plasmas. (10th February 2020) - Chowdhuri, M B; Manchanda, R; Ghosh, J; Jadeja, K A; Patel, Kaushal M; Kumar, Vinay; Patel, Ketan M; Atrey, P K; Joisa, Y Shankara; Bhatt, S B; Tanna, R L
Abstract: The effective charge, Z eff, of the plasmas of the Aditya tokamak has been analyzed to understand its behavior. It has been measured through the monitoring of the visible bremsstruhlang continuum emission around 523.4 nm from the plasma using an optical fiber, interference filter and photo multiplier tube based visible spectroscopic system. It has been found that the values of Z eff fall in the range of 1.7–4.0 and decrease with increasing plasma electron density, n e and the incremental value of Z eff is inversely proportional to n e 2 . The value of Z eff reduces in the range of 1.7–2.5 in the discharges produced after the Li coating compare to the values of 2.0–3.5 range in the discharges before the Li coating in the Aditya tokamak. Details analysis on the contribution to Z eff from various impurities suggests that reduction of Z eff after Li coating is not only due to decrease of oxygen concentration, but also other impurities, such as iron, inside the plasma.